2016
DOI: 10.1002/aelm.201600240
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Electrically Insulating Units in Organic Semiconductor Thin Films for High‐Performance Organic Transistors

Abstract: The electrical properties of organic semiconductors (OSCs), whether they are conjugated small molecules or polymers, can be tailored by incorporating electrically insulating units (EIUs), which are organic moieties consisting of nonconjugated units. EIUs can be introduced to a thin film by synthetically connecting them to the otherwise conjugated OSC molecules or by blending them in as separate EIU molecules with the OSCs during the thin‐film fabrication process. The engineered EIUs are capable of imparting va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 309 publications
(673 reference statements)
2
74
0
Order By: Relevance
“…The ON‐state current level of OFETs with current amplification is directly proportional to μ FET , so increase in μ FET contributes to improvements in the ON‐OFF current ratio, which has a primary role in electronic switching in most OFET applications. There are now a large number of solution‐processed or vacuum‐deposited organic semiconductors (OSCs) with μ FET values on the order of 1–10 cm 2 V −1 s −1 . These values rival or exceed those of benchmark thin‐film amorphous silicon devices (0.5–1 cm 2 V −1 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ON‐state current level of OFETs with current amplification is directly proportional to μ FET , so increase in μ FET contributes to improvements in the ON‐OFF current ratio, which has a primary role in electronic switching in most OFET applications. There are now a large number of solution‐processed or vacuum‐deposited organic semiconductors (OSCs) with μ FET values on the order of 1–10 cm 2 V −1 s −1 . These values rival or exceed those of benchmark thin‐film amorphous silicon devices (0.5–1 cm 2 V −1 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches not only suppress molecular packing in the condensed phase, but also reduce the density of chromophores in the π‐conjugated polymer, resulting in a massive decrease of the inherent electrical properties . To surmount such incompatibilities between the photovoltaic and mechanical properties of semiconductors, several blending methods using rubber‐like plasticizers or elastic polymers were explored ,. Besides, we confirmed that using polymeric additives can help refine bulk heterojunction (BHJ) morphology in blend and enhance the PCE .…”
Section: Figurementioning
confidence: 67%
“…Rather, the donor and acceptor components are typically designed such that upon photoexcitation, the relative energies of the FMOs favor electron transfer from donor to acceptor, while morphology is an aerthought that is optimized via trial and error. 20,23,24 Typically, two component systems are spin-coated together to create blended active layers, and the most common strategies for improving the mixing of donors and acceptors during this process include installing solubilizing side chains on the components, 19,25 solvent annealing, 26 adding insulating polymer llers, 27 adding peptide side chains, 28,29 or, alternatively, covalently linking the two together to create architectures such as diads, 30 triads, 31 donoracceptor alternating polymers, 32 and double-cable polymers. 33 Though these covalent strategies may improve heterojunction interface area, drawbacks include their cumbersome and time consuming syntheses, which limit the ability to establish structure-activity relationships, and their inability to predictably control molecular orientation on the nanoscale and lm structure on the micrometer length scale, which are both necessary to create contiguous and uniform percolation pathways from the site of charge separation to the electrodes.…”
mentioning
confidence: 99%